2015
DOI: 10.7464/ksct.2015.21.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Activity of Cu/Zn Catalyst by Ce Addition for Low Temperature Water Gas Shift Reaction

Abstract: In order to investigate the effect of cerium oxide addition, Cu-ZnO-CeO2 catalysts were prepared using co-precipitation method for water gas shift (WGS) reaction. A series of Cu-ZnO-CeO2 catalyst with fixed Cu Content (50 wt%, calculated as CuO) and a given ceria content (e.g., 0, 5, 10, 20, 30, 40 wt%, calculated as CeO2) were tested for catalytic activity at a GHSV of 95,541 h -1 , and a temperature range of 200 to 400 ℃. Cu-ZnO-CeO2 catalysts were characterized by using BET, SEM, XRD, H2-TPR, and XPS analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The results revealed that Pt/Ce 0 . 5 La 0.5 O 2-δ synthesized by urea co-precipitation had the highest CO conversion activity compared to the other two methods [107].…”
Section: Type Of Metal Oxide Supportmentioning
confidence: 84%
See 1 more Smart Citation
“…The results revealed that Pt/Ce 0 . 5 La 0.5 O 2-δ synthesized by urea co-precipitation had the highest CO conversion activity compared to the other two methods [107].…”
Section: Type Of Metal Oxide Supportmentioning
confidence: 84%
“…8 a-c Electron microscopy analysis of Pt/ceria catalysts prepared by sol-gel after WGS testing [104]. d Temperature dependence of the CO conversion over Au catalysts on Y-doped Ce synthesized by CP [107]. e TEM images of the Cu/CeO 2 catalysts prepared by reverse precipitation method [108].…”
Section: Type Of Metal Oxide Supportmentioning
confidence: 99%